Visualization of Zika Virus Infection via a Light-Initiated Bio-Orthogonal Cycloaddition Labeling Strategy - Zheng, Judun; Yue, Rui; Yang, Ronghua; Wu, Qikang; Wu, Yunxia; Huang, Mingxing; Chen, Xu; Lin, Weiqiang; Huang, Jialin; Chen, Xiaodong; Jiang, Yideng; Yang, Bin; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Zika virus (ZIKV) is a re-emerging flavivirus that leads to devastating consequences for fetal development. It is crucial to visualize the pathogenicity activities of ZIKV ranging from infection pathways to immunity processes, but the accurate labeling of ZIKV remains challenging due to the lack of a reliable labeling technique. We introduce the photo-activated bio-orthogonal cycloaddition to construct a fluorogenic probe for the labeling and visualizing of ZIKV. Via a simple UV photoirradiation, the fluorogenic probes could be effectively labeled on the ZIKV. We demonstrated that it can be used for investigating the interaction between ZIKV and diverse cells and avoiding the autofluorescence phenomenon in traditional immunofluorescence assay. Thus, this bioorthogonal-enabled labeling strategy can serve as a promising approach to monitor and understand the interaction between the ZIKV and host cells.